Artisan, cultural and tourism entrepreneurship. Issue 4 (4th June 2019) - Ratten, Vanessa; Costa, Carlos; Bogers, Marcel
Abstract : Purpose: The purpose of this paper is to focus on emerging research avenues for artisan entrepreneurship. The key findings of the articles in the special journal issue are discussed in terms of potential research issues that need to be discussed in future work. Design/methodology/approach: An overview of the main themes of artisan entrepreneurship in terms of cultural and tourism perspectives is undertaken. This helps to establish artisan entrepreneurship as a new and emerging field of entrepreneurship studies. Findings: There is more interest in artisan entrepreneurship due to its role in revitalizing economies and placing emphasis on cultural heritage and traditions. Originality/value: This paper will provide directions for future research on artisan, cultural and tourism entrepreneurship.